How to Get Rid of Goutweed - Oldenburg, Felix; Landwehrjohann, Max (Satura, 2022)
When his father dies on June 11, 2020, the garden is in immaculate condition. Jasper leans on the garden fence. Wood splinters drill through the thin fabric of his long-sleeve cotton shirt into his forearms. He smells the freshly mown lawn, feels the heat of the stones by the herb bed. He doesn’t dare enter the garden. It’s too much of a risk, for the garden should never look any other way: groomed, cut and kept in shape by his father, every morning between 6 and 7:15.